Optimization Method of Object Packaging in Planning of Mobile Communication Systems Femtocells - Sielivanov, K.; Al-Vandavi Saif Ahmed Iskandar; Moskalets, M. (ХНУРЕ, 2020)
The problem of placing access points of femtocells in the service area of the mobile base station is considered. A method of optimizing the spatial deployment of femtocells using packaging methods is proposed. Based on the method of joining the single femtocell access points, an algorithm for finding and removing potential nested containers has been built. The proposed method of optimizing the spatial placing of femtocells allows to reduce the time of finding the point of installation in order.
Keywords: femtocell; object packaging; planning; access point; container